Anticancer potential of natural bioactive compounds saponins in glioblastoma multiforme - Elsori, Deena; Alshabrmi, Fahad M.; Alharbi, Ahmed M.; Saeed, Mohd; Singh, Ajay; Pandey, Pratibha; Rab, Safia Obaidur; Khan, Fahad (Frontiers in Pharmacology, 2025)
According to the WHO Organization, glioblastoma multiforme (GM) is classified as a grade IV histological malignant tumor of the central nervous system. Numerous genetic abnormalities (tumor cells) and dysregulated cell cycle checkpoints, such as G1/S, have been linked to the progression of glioblastoma multiforme. In addition to tumor removal, glioblastoma multiforme can be treated with chemotherapy and radiotherapy. Immunotherapy and medications that block integrin signaling pathways have also been used. Owing to tumor recurrence, metastasis, and treatment resistance, conventional pharmacological regimens continue to be lethal. Consequently, the quest for an efficacious therapeutic approach for GM remains elusive. Innovative products derived from natural substances have also been proposed as potential remedies. They safeguard glial cells by inducing apoptosis, reducing oxidative stress and neuroinflammation, suppressing proliferation, decreasing pro-oncogenic processes, and enhancing the effectiveness of anticancer therapies. Among various natural compounds, saponins are now being considered for use in cancer treatment. The function and mechanism of action of saponins in cancer have been reported in numerous research findings. These anticancer effects include antioxidant activity, apoptotic induction, cell cycle arrest, and suppression of cellular invasion and migration. This review presents the application of natural saponins as a potential alternative for developing a novel therapeutic strategy that will enhance the treatment options for combating GM in the future.